2013
DOI: 10.1097/brs.0b013e3182913400
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Interbody Fusion of the Cervical Spine With Zero-P Spacer

Abstract: The results of this study confirm biomechanical assumptions associated with the Zero-P spacer. Implantation of this new cage results in setting required biomechanical conditions in the treated segment that are comparable with those when the segment is treated with a dynamic plate. However, the potential of the mentioned implant to reduce the incidence of postoperative dysphagia was not proven on this sample of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Four studies consisting of 381 patients reported the preoperative and postoperative neck NDI (Zero-P group, 180; Plate group, 201)[17, 19, 20, 27]. The fixed-effects model was applied to compare the preoperative or postoperative NDI between the two groups but was accompanied by high heterogeneity (preoperative, I 2 = 94%; postoperative, I 2 = 84%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies consisting of 381 patients reported the preoperative and postoperative neck NDI (Zero-P group, 180; Plate group, 201)[17, 19, 20, 27]. The fixed-effects model was applied to compare the preoperative or postoperative NDI between the two groups but was accompanied by high heterogeneity (preoperative, I 2 = 94%; postoperative, I 2 = 84%).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported a postoperative segmental Cobb’s angle in 163 patients (Zero-P group, 88; Plate group, 75)[16, 26, 27]. The fixed-effects model was applied to compare the postoperative segmental Cobb’s angle between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations